The Utilization of Voluntary Counseling and Testing Through Support and Family Health Care Functions - Ni Putu Wiwik Oktaviani; Ni Luh Putu Devhy; I Made Sudarma Adiputra; Ni Wayan Trisnadewi (Universitas Airlangga, 2021)
Background: The transmission of the Human Immunodeficiency Virus (HIV) from mother to baby is now increasing along with the growing number of HIV-infected women. Approximately 15% of pregnant women living with HIV have accessed antiretroviral (ARV) medicine to prevent transmission of the virus to their babies. Purpose: This study aimed to identify the support and healthcare functions available to pregnant women in using the voluntary counseling test (VCT). Methods: This research was conducted in the working area of Gianyar District health center. The independent variables in this study are family support and family healthcare functions. The dependent variable is the utilization of VCT health service facilities. This study employed a cross-sectional research design. The samples were 108 respondents recruited using a probability sampling technique, namely multi-stage sampling. Bivariate and multivariate analysis were conducted using the chi-square test and logistic regression test. Results: The research variable related to the use of VCT health services with family support showed an odds ratio (OR) = 122, while family healthcare function had an OR = 465. Conclusion: Pregnant women with good family support, good healthcare function, increased maternal age, and early gestational age were more likely to use VCT than when they were in opposite situations.